Constrained autonomy: academics and institutional leaders empowerment in Ethiopia in the context of the Bologna Process. Issue 2 (7th February 2022) - Mekonnen, Geberew Tulu; Kilpatrick, Sue; Kenny, John
ABSTRACT: This study explored academics' and institutional leaders' perception of the empowerment of various actors in Ethiopian higher education institutions. Little is known about university autonomy in Ethiopian higher education in the context of the Bologna Process. Three public universities were selected from the 31 public universities using a stratified sampling technique. A mixed method exploratory research design was employed. The study used descriptive statistics (mean and standard deviation) and inferential statistics (ANOVA and Tukey's posthoc test) for the quantitative data analysis while thematic analysis was used to identify the emerging themes and meanings within qualitative data. The findings of this study showed that the Ethiopian public universities are hierarchal (top-down) in terms of autonomy as power is highly centralized, and the autonomy of the academic units is constrained. Both academics and institutional leaders expressed dissatisfaction with the current situation. They noted the need for more autonomy for the University, which they expected would subsequently lead to them having greater academic freedom. From the findings of the study, there is a critical need for a flexible and responsive system of governance, where academics and institutional leaders are empowered to execute their core activities. University autonomy should be supported by more collegial and less hierarchical systems of governance. The study suggests shared governance or consultative governance for mutual accommodation if Ethiopian universities are to maintain their academic freedom and institutional autonomy and optimize their contribution to national development.